2018
DOI: 10.1111/clr.13273
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of different dental impression techniques for implant‐supported dental prostheses: A systematic review and meta‐analysis

Abstract: Aim: This systematic review and meta-analysis were conducted to assess and compare the accuracy of conventional and digital implant impressions. The review was registered on the PROSPERO register (registration number: CRD42016050730). Material and Methods:A systematic literature search was conducted adhering to PRISMA guidelines to identify studies on implant impressions published between 2012 and 2017. Experimental and clinical studies at all levels of evidence published in peer-reviewed journals were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(144 citation statements)
references
References 78 publications
2
99
1
9
Order By: Relevance
“…Digital workflows play an important role in implant dentistry through acquiring implant positions and displaying them in a virtual model . Scan bodies have been developed to take digital implant scans by creating an accessible surface for optical acquisition and are readily detectable and can be matched with the corresponding digital implant library by the software .…”
Section: Introductionmentioning
confidence: 99%
“…Digital workflows play an important role in implant dentistry through acquiring implant positions and displaying them in a virtual model . Scan bodies have been developed to take digital implant scans by creating an accessible surface for optical acquisition and are readily detectable and can be matched with the corresponding digital implant library by the software .…”
Section: Introductionmentioning
confidence: 99%
“…In dentistry, implant‐supported prostheses can be produced according to a conventional or digital workflow. In each case, impression making is the first step prior to the subsequent fabrication of a dental prosthesis . Both processes have specific advantages and disadvantages.…”
mentioning
confidence: 99%
“…In this context, the open tray technique, has been shown to be superior to the closed tray technique . Furthermore, the kind of impression material, implant level, implant angulation, and transfer copings influence the accuracy of the conventional impression . One study demonstrated no significant difference in the marginal discrepancy of conventional impressions depending on the implant or abutment level .…”
mentioning
confidence: 99%
“…Flugge et al 210 reported on a meta-analysis of the literature addressing the accuracy of different impression techniques for implant-supported dental prostheses. Overall, 59 studies evaluated conventional impressions, 11 digital scans, and 9 compared both techniques.…”
Section: Digital Versus Conventional Workflowmentioning
confidence: 99%